Understanding catalytic effects of bentonite/clinoptilolite on biomass pyrolysis - Mohamed, Badr A.; Ellis, Naoko; Kim, Chang Soo; Bi, Xiaotao (Pergamon Press Ltd., 2019)
Thermogravimetric analysis was performed to differentiate between the thermal and thermo-catalytic decomposition behaviour and kinetics of switchgrass (SG) pyrolysis and catalytic pyrolysis using bentonite or clinoptilolite. Silica sand was tested as an inert material with a thermal conductivity close to bentonite. Using a three-parallel reaction mechanism, it is shown that bentonite and clinoptilolite significantly increased the conversion percentage of all three pseudo-components, while the major difference was found for pseudo-lignin. Silica sand significantly increased the conversion of pseudohemicellulose only. Addition of catalysts increased the conversion of pseudo-lignin by 43 and 36% compared to SG and sand, respectively. The lowest activation energy value of pseudo-lignin was found for 30Bento which was lower by 29 and 25% than SG and sand, respectively. Based on subsequent study using microwave catalytic pyrolysis, it was observed that lignin decomposition was promoted by clinoptilolite and the phenolic compounds particularly the alkylated phenols in bio-oil product were increased by 49% higher than SG, which are primarily derived from lignin. The results obtained from the two-step kinetic model confirmed the speculation based on one-step 3-components kinetics that catalysts are mostly responsible for promoting the catalytic cracking of vapours released from lignin decomposition at high pyrolysis temperatures. (C) 2019 Elsevier Ltd. All rights reserved.